LKPD Elektronik IPA Berbasis Potensi Lokal dengan Model PBL: Upaya Meningkatkan Keterampilan Berpikir Kritis - Ria Rochmi Safitri; Anggraita Febriana Putri; Jumadi; Sabar Nurohman; Ismail Fikri Natadiwijaya; Laifa Rahmawati (Jurnal Pendidikan Indonesia, 2024)
Currently, science learning often uses conventional teaching materials that are less relevant to students' cultural context, thus affecting their involvement in the learning process. In addition, although the PBL model is known to be effective in training critical thinking skills, its implementation in science learning is still limited, especially those that integrate local wisdom as part of the learning content.This research aims to analyze the effect of using electronic LKPD based on the local potential of dome houses with the Problem Based Learning (PBL) model to improve students' critical thinking skills in science learning. This research uses a pre-experimental method with a one group pretest-posttest design. The research sample consisted of 48 class VIII students who were determined through random sampling. Data was collected through tests, with analysis using the Wilcoxon Signed Rank Test. The research found that the use of electronic LKPD based on the local potential of dome houses with the PBL model in science learning was significantly able to improve critical thinking skills, with significance values ​​reaching the high category. All indicators of critical thinking skills experienced an increase in value in this study. Based on these results, learning using electronic LKPD based on local potential with a PBL model can be one of the recommended strategies in science learning. The implications of this research are This research provides guidance in design and use E-Worksheet based on local wisdom with models Problem-Based Learning (PBL) to improve students' critical thinking skills.